Coupled Fixed Point Theorems for (φ, ψ)-Contractive Mixed Monotone Mappings in Partially Ordered Metric Spaces and Applications. (17th March 2014) - Jain, Manish; Gupta, Neetu; Kumar, Sanjay
Abstract : The object of this paper is to establish the existence and uniqueness of coupled fixed points under a (φ, ψ )-contractive condition for mixed monotone operators in the setup of partially ordered metric spaces. Presented work generalizes the recent results of Berinde (2011, 2012) and weakens the contractive conditions involved in the well-known results of Bhaskar and Lakshmikantham (2006), and Luong and Thuan (2011). The effectiveness of our work is validated with the help of a suitable example. As an application, we give a result of existence and uniqueness for the solutions of a class of nonlinear integral equations.